A short History of the Accountancy Profession in Nigeria - Anibaba, Musliu; Institute of Chartered Accountants of Nigeria (Lagos, Nigeria : West African Books Publishers, 1990)
A synopsis of the history of the accounting profession in Nigeria.
Includes index
jbi, 23/03/2018
Loans
Keywords: Accounting; Nigeria